GAMBARAN PENGETAHUAN IBU DALAM PENCEGAHAN PENULARAN FLU SINGAPURA PADA ANAK BALITA - Nabila, Febi; Indriati, Ganis; Sari, Tesha Hestyana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
The Singapore’s flu is a viral infection that occurs in children especially toddlers and is often caused by Coxsackievirus A16 (CV-A16) and Enterovirus 71 (EV-71). Most Singaporean flu cases can be cured by themselves with an incubation period of 3-6 days. Delays in providing proper diagnosis and treatment will cause serious complications and can be fatal to the point of death. This can be a warning to the public, especially mothers, to increase their alertness, and to be able to perform good and correct precautions so that children do not contract and do not transmit Singaporean flu disease to others. The purpose of this study is to find a description of mother's knowledge in the prevention of Singaporean flu transmission in toddlers. Methods: Quantitative research used a descriptive method with a sample of 100 mothers who had toddlers taken with purposive sampling techniques with several inclusion criteria. This study used univariate analysis with descriptive statistics. Results: Most respondents were between the ages of 26-35 years (54%), and had children of more than 1 person (66%), senior high school educated respondents (51%), unemployed respondents (84%) and low family economic status (67%), and the majority of mothers had less knowledge in preventing Singaporean flu transmission in children under five (54%). Conclusion: Mother's knowledge in the prevention of transmission of the Singapore flu in children under five is still low, so mothers are expected to be more alert and to find information about the Singapore’s flu.